2011
DOI: 10.1080/10926755.2011.628266
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Identity as a Protective Factor for Looked After and Adopted Children From Ethnic Minority Groups: A Critical Review of the Literature

Abstract: The development of a strong ethnic identity has been considered to relate to psychological well-being. The aim of this article is to critically review the literature relating to ethnic identity and positive outcomes in looked after and adopted children from ethnic minority groups. A literature search of SCOPUS, PsycINFO, and Medline databases from 2000 to 2010 was conducted to identify qualifying published studies. Studies that pertained to ethnic identity development in children in relation to positive outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Two extensive literature reviews (Castle, Knight, and Watters 2011;Friedlander 1999) report that results on the positive outcomes of a strong heritage ethnic identity in adopted children are mixed. Many studies suggest that the promotion of a strong ethnic identity does not seem to be necessary to psychological well-being in transracial adoptees (Friedlander 1999;Hayes 1993;Mohanty and Newhill 2006).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Two extensive literature reviews (Castle, Knight, and Watters 2011;Friedlander 1999) report that results on the positive outcomes of a strong heritage ethnic identity in adopted children are mixed. Many studies suggest that the promotion of a strong ethnic identity does not seem to be necessary to psychological well-being in transracial adoptees (Friedlander 1999;Hayes 1993;Mohanty and Newhill 2006).…”
Section: Resultsmentioning
confidence: 96%
“…Parental support and openness play a key role in achieving a clear and strong sense of identity for the child. Their acknowledgement of differences with their adopted child, while emphasizing similarities between them and a sense of belongingness, is strongly associated with adoptees' adjustment (Friedlander et al 2000;Benson, Sharma, and Roehlkepartian 1994;Despeignes 1993;Harf, Taïeb, and Moro 2006;Juffer 2006;Kim 1977;Cederblad et al 1999;Yoon 2000;Baden 2002;Castle, Knight, and Watters 2011).…”
Section: Resultsmentioning
confidence: 96%
“…The adoptive family appears to play a key role in the development of ethnic identity and self-esteem (Castle et al 2011). Some studies have shown that transracial adoptive parents engage in cultural socialization practices with their children (Carstens and Julia 2000;Rojewski and Rojewski 2001).…”
Section: Cultural Socializationmentioning
confidence: 97%
“…There has been an increase in the numbers of domestic and international transracial adoptions. The number of US adoptions from foreign countries has exceeded 20,000 per year since 2001 (Castle, Knight, and Watters 2011;Kim 2007Kim , 2009. In 2003, 15% of all foster care adoptions in the US were transracial and approximately 10% of the Korean American population were adopted from South Korea (Lee and Quintana 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Houston and Kramer (2008) discussed the long-term needs of foster care to adoption families, emphasizing the positive impact continued contact with adoption professionals can have on stability in foster to adopt families. Another review of the literature looked for themes among multiple studies on ethnic identity and its effect on adoptive families (Castle, Knight, & Watters, 2011). An adoptive family issue, with a recurring presence in the literature, focuses on parenting issues in adoptive families, especially the connection between adoptive parent-child relationships and conflict/stress (Klahr, McGue, Iacono, & Burt, 2011;Rushton, Monck, Upright, & Davidson, 2006;Viana & Welsh, 2010).…”
mentioning
confidence: 99%